A newly identified cryogenian (ca. 806 ma) basement tonalite gneiss from the Eastern Karakoram, NW India: Constraints from geochemistry and zircon U-Pb geochronology - Pundir, Shailendra; Adlakha, Vikas; Kumar, Santosh; Singhal, Saurabh; Das, Satyabrata (Frontiers in Earth Science, 2022)
The Karakoram Terrane (KT) represents the southern margin of the Eurasian Plate, mainly consisting of Late Jurassic-Early Cretaceous subduction-related granites and post-collisional Miocene leucogranites, which intrude the Late Neo-Proterozoic basement. We report for the first time the existence of the Cryogenian KT basement as recorded from the geochemistry and geochronology of tonalite gneiss (ca. 806 Ma) in the southeastern Karakoram terrane, NW India. Geochemically, the studied tonalite gneiss is slightly peraluminous (Molar Al2O3/CaO+Na2O+K2O=1.1), calc-alkaline volcanic-arc granitoid, strongly fractionated REE (LaN/YbN=33.99), and high Sr/Y =19.75, more akin to its affinity with Tonalite–trondhjemite–granodiorite (TTG)/adakite. The whole-rock elemental data suggest that tonalite gneiss is more likely sourced from ancient mafic lower crust where garnet remained in the residue. The petrogenetic modeling of REE suggests that the melt similar to the observed tonalite gneiss can be generated through ~50 % partial melting of a mafic lower crust with garnet, clinopyroxene, and amphibole assemblage. The synthesis and comparison of present and published Proterozoic magmatic records on the rocks from KT strongly dictate that the produced partial melt similar to observed tonalite gneiss most likely served as the parental melt for the development of TTGs in the Southern Pamir and more evolved granitoid in the Central Tibetan terrane. We propose that the studied tonalite gneiss from the southeast Karakoram is a product of Neoproterozoic Andean-type orogeny formed on the northwestern margin of the Rodinia supercontinent. Thus, our study favors the first time, the position of KT within the Cimmerian belt along with other East Asian continental blocks.